If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50(40) = 0.20(40 + -1m) + 0.80m Multiply 0.50 * 40 20 = 0.20(40 + -1m) + 0.80m 20 = (40 * 0.20 + -1m * 0.20) + 0.80m 20 = (8 + -0.2m) + 0.80m Combine like terms: -0.2m + 0.80m = 0.6m 20 = 8 + 0.6m Solving 20 = 8 + 0.6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-0.6m' to each side of the equation. 20 + -0.6m = 8 + 0.6m + -0.6m Combine like terms: 0.6m + -0.6m = 0.0 20 + -0.6m = 8 + 0.0 20 + -0.6m = 8 Add '-20' to each side of the equation. 20 + -20 + -0.6m = 8 + -20 Combine like terms: 20 + -20 = 0 0 + -0.6m = 8 + -20 -0.6m = 8 + -20 Combine like terms: 8 + -20 = -12 -0.6m = -12 Divide each side by '-0.6'. m = 20 Simplifying m = 20
| 8y+5=24+2y | | 4a+b=20 | | -13x+21x+2x+15=-45 | | -16k+33k-80k+76k=-52 | | 3a+b=15 | | x^2+-2x-5.25=0 | | x^2+-2x-5.25=0 | | -4x+3(2x-1)=-5 | | 3(2x-4)=2(2x-10) | | 9-(-5+x)-7x=50 | | 5x+6+5=2 | | 3x+2a=2a+24 | | 114s+14s+12s=1 | | 2x^2-10x^2+9x= | | 4x+(x-5)(x+4)+15=(3-x)(x+3)+(x+6)(x-3) | | 2a^2-18a+20.25=0 | | x-3(17)=81 | | F(X)=(32-x)(40-x) | | x+2=5x+22 | | 2kx^2+kx-x=0 | | 3X+1=48 | | 4x+y=-x+9 | | 2x+3=61 | | 6(-2-9k)= | | 3x-1.66=-7(3.5x-3)-3 | | 2(6+5x)=102 | | 4x=81+x | | -29x+6.1=-5(5.8x+2.2)-0.3 | | a+0.05a= | | -45x-1=9(-5x+1)-4 | | -15=5x+10 | | (x+3)(x-4)=-12 |